Integration of artificial intelligence and triple integral in aerodynamic analysis - Sayfullaeva, Maftuxa; Tadjibaeva, Shaxzadakhan; Abduganieva, Ozoda (MMIT Proceedings, 2025)
This article examines the possibilities of spatial analysis of airflow based on triple integrals and the effective use of artificial intelligence tools in this process. The distribution of air density and velocity fields in three-dimensional space is expressed through mathematical modeling, and calculations are performed quickly and visually using artificial intelligence. The article highlights the interactive and practical approach of engineering education through the integration of modern technologies in solving aerodynamic problems, in particular AI (Artificial intelligence) algorithms, into the educational process. The research results propose new approaches to the modeling of real systems through automated solutions of spatial integral analysis.